Lipid is heterogeneously distributed in muscle and associates with low radiodensity in cancer patients. Issue 3 (27th January 2020) - Bhullar, Amritpal S.; Anoveros‐Barrera, Ana; Dunichand‐Hoedl, Abha; Martins, Karen; Bigam, David; Khadaroo, Rachel G.; McMullen, Todd; Bathe, Oliver F.; Putman, Charles T.; Clandinin, Michael T.; Baracos, Vickie E.; Mazurak, Vera C.
Abstract: Background: Low muscle radiodensity is associated with mortality in a variety of cancer types. Biochemical and morphological correlates are unknown. We aimed to evaluate triglyceride (TG) content and location as a function of computed tomography (CT)‐derived measures of skeletal muscle radiodensity in cancer patients. Methods: Rectus abdominis (RA) biopsies were collected during cancer surgery from 75 patients diagnosed with cancer. Thin‐layer chromatography and gas chromatography were used for quantification of TG content of the muscle. Axial CT images of lumbar vertebra were used to measure muscle radiodensity. Oil Red O staining was used to determine the location of neutral lipids in frozen muscle sections. Results: There was wide variation in RA radiodensity in repeated measures (CV% ranged from 3 to 55% based on 10 serial images) as well as within one slice (CV% ranged from 6 to 61% based on 10 subregions). RA radiodensity and total lumbar muscle radiodensity were inversely associated with TG content of RA ( r = −0.396, P < 0.001, and r = −0.355, P = 0.002, respectively). Of the total percentage area of muscle staining positive for neutral lipid, 54 ± 17% was present as extramyocellular lipids (range 23.5–77.8%) and 46 ± 17% (range 22.2–76.5%) present as intramyocellular lipid droplets. Conclusions: Repeated measures revealed wide variation in radiodensity of RA muscle, both vertically and horizontally. Low muscle radiodensity reflects high level of TG in patients with cancer. Non‐uniform distribution of intramyocellular and extramyocellular lipids was evident using light microscopy. These results warrant investigation of mechanisms resulting in lipid deposition in muscles of cancer patients.